AN ANALYTICAL STUDY OF COUNSELING COMMUNICATION STYLE IN THE HADITH NARRATING THE 100-MURDERER STORY - Sukandar, Warlan; Budiman, Arif; Bin Abdul Aziz, Abdul Rashid (INSTITUT AGAMA ISLAM NEGERI METRO, 2024)
Hadith, as the second source of Islamic teachings, is full of scientific values in communication and counseling. This study aims to examine the counseling communication style in the hadith and analyze the story of the repentance of the murderer of a hundred people as an example of application in counseling. This study uses a library research method, a type of study of revelation texts with a sociological and interpretive approach. The data analysis technique for this study uses the content analysis method. The results of the study identified eight styles of counseling communication in the hadith of the story of the repentance of the killer of a hundred people, namely empathetic communication, firm and clear communication, supportive communication, communication providing direction, inspiring communication, communication using stories, reflective communication, and positive communication. In today's contemporary context, this communication style can be applied to clients who come from various backgrounds (cultural, social and economic), dealing with complex problems, online counseling and is also suitable for use in efforts to empower clients.